2004
DOI: 10.1111/j.1464-5491.2004.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced forearm reactive hyperaemia in normoalbuminuric subjects with Type 1 diabetes and retinopathy

Abstract: Retinopathy in subjects with Type 1 diabetes mellitus may reflect a generalized process of endothelial dysfunction, even in the absence of microalbuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Gibney et al 6 evaluated the forearm vasodilatory response to reactive hyperaemia (RH) in patients with type 1 diabetes. RH was evaluated using strain-gauge plethysmography, and subjects with retinopathy showed reduced forearm RH responses compared with those with no retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Gibney et al 6 evaluated the forearm vasodilatory response to reactive hyperaemia (RH) in patients with type 1 diabetes. RH was evaluated using strain-gauge plethysmography, and subjects with retinopathy showed reduced forearm RH responses compared with those with no retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Most 5–9 but not all 10–12 studies have found endothelial function to be more markedly impaired in subjects with diabetic microangiopathy. Metabolic alterations of diabetes produce various functional and structural changes at the arteriolar and capillary levels, including the basement membrane, the smooth muscle cells and, in particular, the endothelial cells 2,13 .…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of this response by strain‐gauge plethysmography is a non‐invasive marker of endothelial‐dependent vasodilatation 27. Post‐hyperaemia forearm blood flow only reflects the vasomotor component of endothelial function, so these findings should not be extrapolated to other endothelial functions 28…”
Section: Discussionmentioning
confidence: 99%